Antibiogram profiles of pathogenic and commensal bacteria in goat and sheep feces on smallholder farm - Basnet, Ashesh; Kilonzo-Nthenge, Agnes (Frontiers in Antibiotics, 2024)
The increase of antimicrobial resistance (AMR) in zoonotic pathogens poses a substantial threat to both animal production and human health. Although large-scale animal farms are acknowledged as major reservoirs for AMR, there is a notable knowledge gap concerning AMR in small-scale farms. This study seeks to address this gap by collecting and analyzing 137 fecal samples from goat and sheep farms in Tennessee and Georgia.Method: Bacteria were identified using culture-dependent methods and polymerase chain reaction (PCR), and antimicrobial susceptibility testing (AST) was performed using the Kirby-Bauer Disk Diffusion method.The prevalence of E. coli (94.9%) in goats and sheep significantly exceeded (p < 0.05) that of S. aureus (81.0%), Shigella (35.0%), S. saprophyticus, and Salmonella (3.0%). Salmonella occurrence in goat feces (2.2%) was higher than in sheep (0.8%). Notably, 27% of goats and 8% of sheep tested positive for Shigella spp., while 60% of goats and 21% of sheep tested positive for S. aureus. Antibiotic resistance was observed primarily against ampicillin (79.4%), vancomycin (65.1%), and gentamycin (63.6%), significantly surpassing (p < 0.05) resistance to tetracycline (41.6%) and imipenem (21.8%). The penicillin (79.4%), glycopeptide (65.1%), and aminoglycoside (63.6%) antibiotic classes displayed significantly higher (p < 0.05) resistance compared to tetracyclines (45.7%) and carbapenem (21.8%). Our findings suggest that goats and sheep feces may serve as source for multidrug-resistant bacteria, raising concerns about the potential introduction of their fecal matter into soil, water, and eventually to the food chain. This highlights the need for proactive measures to address and mitigate AMR in goats and sheep within small-scale farms.